Under the Radar: Pentecostalism in South Africa and Its Potential Social and Economic Role - The Centre for Development and Enterprise, South Africa (Pentecostalism and Prosperity: The Socio-Economics of the Global Charismatic Movement, 2012)
[Case Study] The durability and adaptability of religious faiths and their dynamic interaction with other powerful forces in this globalizing world have begun to attract the attention of researchers. Among them are those whose interest lies in understanding the social, economic and political factors that promote or retard development in emerging societies. One specific focus of this kind of research has been the spectacular growth of Pentecostal Christian churches in developing societies in Latin America and the Far East. The CDE team was led by Ann Bernstein. This paper includes the findings of a variety of research papers commissioned by CDE. The project was managed by Stephen Rule and Timothy Clynick. Contributions were made by Lawrence Schlemmer, Tony Balcomb, Phil Bonner, Tshepo Moloi, Godfrey Dlulane, Timothy Clynick, William Domeris, Paul Germond, Steven de Gruchy, Riaan Ingram, Hudson Mathebula, Lehasa Mokoena, Attie van Niekerk, Monica Bot, Montagu Murray, and Sandy Johnston. The project was advised by Professor Peter Berger of Boston University—CDE’s international associate—and Professor James Hunter of the University of Virginia.
paid
Keywords: Black Economic Empowerment; Protestant Ethic; Religious Faith; Social Capital; South African Society